Enhancing superconductivity in SrTiO 3 films with strain - Ahadi, Kaveh; Galletti, Luca; Li, Yuntian; Salmani-Rezaie, Salva; Wu, Wangzhou; Stemmer, Susanne (Science advances, 2019)
A doubling of the superconducting transition temperature occurs in strained SrTiO 3 films, which are known to become ferroelectric. The nature of superconductivity in SrTiO 3 , the first oxide superconductor to be discovered, remains a subject of intense debate several decades after its discovery. SrTiO 3 is also an incipient ferroelectric, and several recent theoretical studies have suggested that the two properties may be linked. To investigate whether such a connection exists, we grew strained, epitaxial SrTiO 3 films, which are known to undergo a ferroelectric transition. We show that, for a range of carrier densities, the superconducting transition temperature is enhanced by up to a factor of two compared to unstrained films grown under the same conditions. Moreover, for these films, superconductivity emerges from a resistive state. We discuss the localization behavior in the context of proximity to ferroelectricity. The results point to new opportunities to enhance superconducting transition temperatures in oxide materials.